Effectiveness of Early Warning Score (EWS) Implementation in Improving the Accuracy of Early Preeclampsia Detection in Antenatal Care - Rapida Saragih; Christin Jayanti; Sitha Paradilla Delarosa (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Preeclampsia remains a major contributor to the maternal morbidity and mortality rates, in which the delayed detection at the primary healthcare level often leads to late referrals and further severe complications. Objective: This study aimed to evaluate the effectiveness of an Early Warning Score (EWS) implementation for improving the accuracy of early preeclampsia detection during Antenatal Care (ANC) services at a Community Health Center. Methods: This study employed a pre-experimental one-group pretest-posttest design. A total of 20 pregnant women were selected through the total sampling. Detection accuracy was defined as the precision in systematically integrating vital signs and subjective clinical symptom assessments compared to conventional methods. Data were analyzed using a paired sample t-test with a significance level of 0.05. Results: The findings showed a significant improvement in the mean accuracy score for early detection from 62.45 (pretest) to 78.90 (posttest), with a mean difference of 16.45 (p < 0.05). Power analysis revealed a Cohen’s d value of 2.12, indicating that the EWS intervention had a large clinical effect size in enhancing the provider detection sharpness. Conclusion: The EWS implementation proved to be significantly effective for improving the accuracy of early preeclampsia detection within the scope of ANC services at the Mandala Community Health Center. Integrating EWS into the routine ANC practices is highly recommended to support a timely clinical decision-making and to prevent severe maternal complications Keywords: Early Warning Score, Preeclampsia, Antenatal Care, Early Detection, Maternal Health